DESIGN DATABASE FOR APPLICATION INTRODUCTION OF BOGOR BATIK MOTIF WEB-BASED - Adriana Sari Aryani; Irma Anggraeni (Universitas Pakuan, 2019)
Bogor batik motifs are inspired by the legacy of the kingdom of Pakuan, historical objects, phenomena, and culture. One of the famous motifs is the Kujang Kijang motif. In addition to deer motifs, Batik Bogor also has other unique motifs such as the pilsau cleaver motif and drizzling rain. Bogor Batik motifs applied in batik scratches are mostly symbols of the City of Bogor itself. The deer head motif is a mirror of the Bogor Palace, the lotus motif becomes a symbol of the Bogor Botanical Gardens, the cleaver blade as a symbol of the city of Bogor and the drizzle motif as the designation of the city of Bogor. Database Design is the process of determining the content and data settings needed to support various system designs. The purpose of Database Design is: to fulfill information that contains specific user needs and their applications. facilitate understanding of information structures, support processing needs and multiple object appearance (response time, processing time, and storage space). In the web-based Bogor batik motif introduction application using the DBS SQL Server. The advantages of Microsoft SQL Server one of which can work very well on all windows operating systems.